QSPR Modeling of Fungicides Using Topological Descriptors - Saima Parveen; Fatima Saeed; Fozia Bashir Farooq; Nusrat Parveen; Nazeran Idrees; Sumiya Nasir; Rakotondrajao Fanja (International Journal of Analytical Chemistry)
A topological index is a real number that is obtained from a chemical graph’s structure. Determining the physiochemical and biological characteristics of a variety of medications is useful since it more accurately represents the theoretical characteristics of organic molecules. This is accomplished using degree-based topological indices. The QSPR research has improved the structural understanding of the physiochemical properties of fungicides. Thirteen fungicides are examined for some of their physiochemical properties, and a QSPR model is built using nine of the drugs’ topological indices. Here, we examine the degree to which the topological indices and physiochemical attributes are connected. To do this, we create networks connecting each of the topological indices to the properties of fungicides and computationally construct topological indices of the drugs mentioned above. According to this QSPR model, the melting point, boiling point, flash point, complexity, surface tension, etc. of fungicides are strongly connected. It was discovered that the topological indices (TIs) applied to the fungicides more accurately represent their theoretical features and show a strong correlation with their physical attributes.